2022
DOI: 10.1002/pc.27093
|View full text |Cite
|
Sign up to set email alerts
|

Properties and characterization of carrot nanocellulose/starch biopolymer nanocomposites

Abstract: In order to produce bio‐nanocomposites for potential food packaging applications, nanocellulose (NC) was extracted from carrot pulp and different weight fractions of NC (5, 7, and 10 wt%) were incorporated into corn starch, either with or without thyme extract, using the solvent casting process. The particle size of the extracted NC (200–300 nm) was determined using the dynamic light scattering test, and field emission scanning electron microscopy confirmed the spherical morphology of the NC, which was success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Nanocellulose has many advantages, such as comprehensive source, excellent mechanical properties, green and degradable, and low cost, and is considered an ideal filler for improving the mechanical properties of composites. [14][15][16][17] In recent years, research on nanocellulose as a filler for light-cured 3D printing has gradually developed, and its application has been reported in several kinds of literature. Sandeep et al [18] first reported the application of CNC as filler in SLA printing method.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocellulose has many advantages, such as comprehensive source, excellent mechanical properties, green and degradable, and low cost, and is considered an ideal filler for improving the mechanical properties of composites. [14][15][16][17] In recent years, research on nanocellulose as a filler for light-cured 3D printing has gradually developed, and its application has been reported in several kinds of literature. Sandeep et al [18] first reported the application of CNC as filler in SLA printing method.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Several studies have been conducted to replace glass fiber with bio/natural fibers. [7][8][9][10] However, it has declined the mechanical properties of hybrid composites. A survey by Ashish kumre [11] on sisal glass fiber reinforced polymer composites concluded that the sisal/glass fiber composite showed lower mechanical properties than the glass fiber control sample composite.…”
Section: Introductionmentioning
confidence: 99%